Brazilian spotted fever: A spatial analysis of human cases and vectors in the state of São Paulo, Brazil. (11th June 2020) - Ribeiro, Claudia Mello; da Costa, Veruska Maia; de Carvalho, Jonas Lotufo Brant; Mendes, Rodrigo Guerrero; Bastos, Paula Andrea de Santis; Katagiri, Satie; Amaku, Marcos
Abstract: Brazilian spotted fever (BSF) is a highly lethal disease caused by Rickettsia spp. and is transmitted by ticks of the genus Amblyomma . Understanding the epidemiology of BSF in each region can help direct health surveillance actions. The objective of this study was to determine the spatial distribution of vectors and the incidence of BSF in the state of São Paulo. Spatial analysis included confirmed BSF cases between 2009 and 2019; occurrences were registered by municipalities of the state. There were 752 confirmed BSF cases, with incidences ranging between 0.01 and 10.37/10, 000 inhabitants. Moran's Global Index for BSF was 0.20 ( p  = .001), which was indicative of spatial dependence. Moran's map located a cluster of 20 high priority municipalities for BSF and showed that Amblyomma sculptum is the vector involved in Rickettsia rickettsii transmission in these locations. Spatial analysis identified clusters formed by 47, 20 and seven significant municipalities for the presence of A. sculptum, Amblyomma aureolatum and Amblyomma ovale vectors, respectively. Surveillance and prevention actions are necessary in areas that are at high risk for BSF and in areas where the presence of vectors was significant.